Tanker om en islandsk fremmedordbog - Kvaran, Guðrún (Nordiske Studier i Leksikografi, 2001)
The topic of this paper is the definition of the term ’dictionary of foreign words’ in HSK and NLO. The definitions of the terms fremmedord/Fremdwort and låneord/Lehnwort in some German and Danish dictionaries are also considered. Åt the end of the paper, the discussion tums to the possibility of making a dictionary of foreign words for lcelandic. One term, tökuoro (’Ioan word’) is used both for foreign words and loanwords, and the conclusion is that for lcelandic the concept dictionary oj loanwords is more to the point than the concept of a dictionary oj joreign words. Such a dictionary should contain information both on actual loanwords, i.e. words that have been adapted to Icelandic phonology and morphology, etc., and truly foreign words, which have not done so.